Desperate characters ebook - Fox, Paula (2011)
One of The Atlantic's Great American Novels One of the New York Times' 25 Most Significant New York City Novels From the Last 100 Years "A towering landmark of postwar Realism...A sustained work of prose so lucid and fine it seems less written than carved." —David Foster Wallace Otto and Sophie Bentwood live in a changing neighborhood in Brooklyn. Their stainless-steel kitchen is newly installed, and their Mercedes is parked curbside. After Sophie is bitten on the hand while trying to feed a stray, perhaps rabies-infected cat, a series of small and ominous disasters begin to plague the Bentwoods' lives, revealing the fault lines and fractures in a marriage—and a society—wrenching itself apart. First published in 1970 to wide acclaim, Desperate Characters stands as one of the most dazzling and rigorous examples of the storyteller's craft in postwar American literature — a novel that, according to Irving Howe, ranks with "Billy Budd, The Great Gatsby, Miss Lonelyhearts, and Seize the Day."